Seasonal variation of soil respiration in a tropical coastal shelter forest and its responses to environmental factors - Chen, Haihui; Tian, Leyu; Chen, Yiqing; Chen, Zongzhu; Nong, Shouqian; Lin, Zhipan; Lei, Xiangling; Jia, Junting; Su, Shaofeng (Frontiers in Plant Science, 2026)
IntroductionTropical coastal shelter forests exhibit unique environmental characteristics and material cycling processes. However, the seasonal dynamics and environmental drivers of soil respiration in these ecosystems remain poorly understood. This study investigated the spatial variation in soil respiration rates across typical tropical coastal shelter forest stands, characterized their seasonal patterns, clarified the roles of soil temperature and soil moisture, and identified the responses of soil respiration to environmental factors during the dry and wet seasons.MethodsFour typical tropical coastal shelter forests in Wenchang, Hainan, Casuarina equisetifolia forest (CA), Cocos nucifera forest (CO), mixed forest (MF), and secondary forest (SF), were monitored through monthly soil respiration measurements over one year. By integrating soil temperature, soil moisture, soil chemical properties, and climatic variables, we analyzed spatiotemporal variations in soil respiration rates and their environmental controls using regression analysis and a random forest model.ResultsSoil respiration rates showed pronounced spatial variation among forest types, with the SF stand exhibiting substantially higher soil respiration and annual CO2 emissions than the others. Soil respiration, soil temperature, and soil moisture all displayed clear seasonal patterns, with markedly higher values during the wet season (May–October) than during the dry season (November–April). Soil temperature was the dominant driver of seasonal variation, showing a highly significant exponential positive relationship with soil respiration and explaining 57.2–84.8% of its variation. In contrast, soil moisture had much weaker explanatory power (1.8–14.4%), although temperature and moisture exhibited synergistic effects. Soil organic matter was identified as a key factor underlying spatial variation across stands, whereas seasonal changes in precipitation and soil pH contributed significantly to differences between the dry and wet seasons.DiscussionThese findings improve our understanding of carbon cycling processes in tropical coastal shelter forests and provide a scientific basis for adaptive forest management under global climate change. The pronounced spatial variation in soil respiration among forest types highlights the importance of species composition and stand structure in regulating coastal carbon budgets. Future management strategies should incorporate these elements to enhance carbon sequestration and strengthen ecosystem resilience to climatic stressors.